Numerical simulation of free-convection flow near vertical heating surface - Dmitry V Bagaev (Труды Крыловского государственного научного центра, 2018)
Object and purpose of research. This work discusses numerical simulation specifics of free-convection flow near vertical heating surface in different CFD software codes. The purpose of this work is to assess possibility of applying semi-empirical turbulence model for position prediction of laminar-turbulent transition of free-convection flow near vertical heating surface. Materials and methods. Parameters of free-convection turbulent flow in the air near vertical heating surface are found from the numerical solution to the system of differential equations in Boussinesq approximation, closed by the turbulence model. Two turbulence models were investigated: k-ω Menter SST and low-Reynolds turbulence model k-eps. Main results. CFD simulation results for turbulent boundary layer on heated plate in the air, obtained in different CFD codes have shown that k-ω Menter SST model does not yield any clear laminar-turbulent transition, whereas in the k-eps model the position of this transition point shifts up the plate as the number of iterations increases. Temperature fields were conservative, so they have shown a good correlation with the experiment in both models. Conclusion. Numerical simulation of free-convection flow near vertical heated surface have shown that k-eps low-Reynolds turbulence models can have spontaneous transition to the turbulence, however, the point of this transition depends not only on the turbulence model, but also on the layout, the mesh, the depth of convergence, as well as on other numerical peculiarities of the calculation algorithm. Without introduction of additional disturbances, semi-empirical turbulence model cannot reliably predict the position of laminar-turbulent transition point.